Pola Komunikasi Guru Terhadap Murid di SLB-C Alpa Kumara Wardhana Kumara 1 Surabaya Pascapandemi Covid-19 - Umar, Audy Maulidya; Wulandari , Anita Agustina (LPPM Stikosa-AWS, 2024)
Communication is one of the important things in the learning process or education to improve communication effectiveness strategies in education. The theory used in this study is the Theory of Communication Patterns and Instructional Theory. This research was conducted using the case study method which is a type of descriptive qualitative research. The subjects in this study used interviews with 4 informants. Based on this research, it can be concluded that the pattern of teacher-student communication during the Covid-19 pandemic cannot use the media as a learning tool. Each informant had the same reason, namely deciding to study face-to-face. The four informants had differences in face-to-face learning strategies. Informant 1 freed the teachers to process learning strategies in communication patterns for their students by their vision and mission so that they could develop students' mental or motor skills. Informants 2 and 4 have the same strategy in teaching and learning by using games that make learning more fun and not boring. Meanwhile, informant 3 prefers to discuss with his students so that his students are used to conveying their feelings or emotions. This pattern of communication aims to develop memory for mentally retarded children and to be responsible and to become children who do not depend on other people in society.